Can the Monkeypox virus pose a potential threat for Pakistan with new emerging cases? - Haiqa Zulfiqar; Uzma Aslam; Yusuf Hasan Ali (Journal of the Pakistan Medical Association, 2023)
Madam, Monkeypox (MPX) is a viral disease belonging to the orthopoxvirus genus with a clinical presentation strikingly similar to that of smallpox which includes fever, rash and lymphadenopathy [1]. The disease is primarily transmitted through direct contact with an infected person, animal, or contaminated material. Recently, Pakistan reported its first two confirmed cases of Monkeypox, and there has been a global outbreak of over 78,000 people infected [2]. Given the statistics, Pakistan should also take preventive actions to control the country-wide spread of the disease. The symptoms of the Monkeypox virus usually begin within a week but may range between 1-21 days after the initial exposure. Initial signi in most individuals is a rash beginning on the face and eventually spreading over the body extending to the palms and soles. The distinct lesions typically appear in stages, beginning with macular, then papular, then vesicular and eventually pustular. Moreover, there can be serious complications including pneumonitis, encephalitis, sight-threatening keratitis and secondary bacterial infections [3]. Cases in the current outbreak have been atypical, with the characteristic rash starting in the genital and perianal areas with or without dissemination to other body parts[4]. The clinical recognition of Monkeypox can be challenging especially in resource-poor endemic regions. Diagnosis is usually done through identification of viral DNA by collecting swabs from the crusts of lesions. According to the Center for Disease Control and Prevention (CDC), no specific vaccine or treatment for the Monkeypox virus is currently available.[5] Prevention is better than cure, it is important to highlight the need for better surveillance and early detection systems nationwide. Promoting campaigns on both small and large scales is crucial to raise awareness about the disease. These campaigns can include awareness sessions in educational institutions and setting up roadside camps in high-risk areas. The public should be advised to take necessary precautions to protect themselves and their communities by restraining contact with infected individuals and practicing isolation if infection is suspected. Front- line health officials are particularly vulnerable and should follow strict standard operating procedures, while airports should be closely monitored for potential cases. While the world is still challenged by the COVID19 pandemic, the emergence of new outbreak by monkeypox virus has raised concerns and therefore, it is high time for the government to plan and implement appropriate actions on emergency basis to control the spread of this disease.